2015
DOI: 10.2298/vsp140223064m
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors and prognostic implications of bleeding complicating primary percutaneous coronary intervention

Abstract: Patients of advanced age, female gender, with baseline anemia and elevated WBC count and those with Killip class II-IV at presentation are at particularly high risk of bleeding after primary PCI. Bleeding is associated with adverse outcome and may be an important marker of patient frailty, but it is not a true independent predictor of mortality/MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Anticoagulant treatment used in general high-risk interventions is similar to the method used in conventional interventions. The activated coagulation time in such patients must be maintained over 300 sec using unfractionated heparin (11). Aspirin should be administered routinely, while thienopyridine-type drugs (clopidogrel, ticagrelor) through stent implantation are routinely used.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant treatment used in general high-risk interventions is similar to the method used in conventional interventions. The activated coagulation time in such patients must be maintained over 300 sec using unfractionated heparin (11). Aspirin should be administered routinely, while thienopyridine-type drugs (clopidogrel, ticagrelor) through stent implantation are routinely used.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 The incidence of bleeding in patients with ACS and primary PCI is up to 14%, varying from 0.2 to 9.1% for major bleeding. 67,68 Bleeding complications, both access and nonaccess site bleeding, are independent risk factors for periprocedural mortality (RR, 4.06; 95% CI, 3.21-5.14 vs. RR, 1.71; 95% CI, 1.37-2.13). 69 Patients with major bleeding events have a significantly higher 30 days mortalitity compared with patients without bleeding (12.8 vs. 2.5%).…”
Section: Assessment Of Effects Of Antiplatelet Therapy In High-risk Pmentioning
confidence: 99%
“…65,66 The most important predictors of bleeding are summarized in ►Table 4. 11,57,67,70,71 New antiplatelet agents (e.g., ticagrelor and prasugrel) provide more rapid and higher degree of ADP-mediated inhibition of platelet aggregation than clopidogrel, and are superior to clopidogrel for preventing ischemic complications, but they are also associated with higher risks of bleeding. 66,70 Administration of clopidogrel in patients with the noted risk factors for bleeding (►Table 4) can be better managed with the more potent antiplatelet agents, especially as a part of the DAP.…”
Section: Assessment Of Effects Of Antiplatelet Therapy In High-risk Pmentioning
confidence: 99%
“…Lao D et al further demonstrated that leukocytosis is an independent predictor in CAD patients after PCI [6]. A large number of recent studies confirmed that the increase in baseline WBC count is associated with the occurrence of adverse clinical outcomes after PCI in patients with CAD [7][8][9].…”
Section: Introductionmentioning
confidence: 99%